THE EFFECT OF SEVERAL PLANTING MEDIA ON THE PERFORMANCE OF MELON (Cucumis melo L.) MICROGREENS - Mardiana, Anissa; warid, warid (Universitas Trilogi, 2023)
Microgreens are vegetables that are harvested at young age with the cotyledons fully blooming but the true leaves not yet growing. Microgreens can be produced from several grain commodities such as melon seeds. In fact, melon seeds can be used as raw material of microgreens which have high economic value. There is limited information regarding melon seeds to make microgreens, regarding the use of planting media in the microgreens production, so research needs to be carried out regarding several planting media effect on the performance of microgreens. The research was conducted at the Experimental Garden and Integrated Laboratory of the Agroecotechnology Study Program, Trilogy University from March to April 2021. The research used Complete Randomized Block Design (CRBD) with two-factor and triplicate . The first factor was the type of melon which consists of mesh melon and golden melon. The second factor was the planting medium which consists of 4 types, namely, husk charcoal, sand, rockwool and zeolite. The research results showed that the planting medium and type of melon had a significant effect on the production of melon microgreens. The best medium for producing golden melon microgreens was sand, while for mesh melons was charcoal husks.